Comparative Genomics Analysis of Streptomyces Species Reveals Their Adaptation to the Marine Environment and Their Diversity at the Genomic Level - Tian, Xinpeng; Zhang, Zhewen; Yang, Tingting; Chen, Meili; Li, Jie; Chen, Fei; Yang, Jin; Li, Wenjie; Zhang, Bing; Zhang, Zhang; Wu, Jiayan; Zhang, Changsheng; et al. (Frontiers in Microbiology, 2016)
Over 200 genomes of streptomycete strains that were isolated from various environments are available from the NCBI, and yet little is known about the characteristics that are linked to marine adaptation in marine-derived streptomycetes. The particularity and complexity of the marine environment suggest that marine streptomycetes are genetically diverse. Here, we sequenced 9 strains from the Streptomyces genus that were isolated from different longitudes, latitudes, and depths of the South China Sea, and we compared these strains to 22 streptomycete strains that were downloaded from the NCBI. Thirty-one streptomycete strains are clearly grouped into a marine-derived subgroup and multiple source subgroup-based phylogenetic tree. The phylogenetic analyses have revealed the dynamic process underlying streptomycete genome evolution, and lateral gene transfer is an important driving force during the process. Pan-genomics analyses have revealed that streptomycetes have an open pan-genome, which reflects the diversity of these streptomycetes and guarantees the species a quick and economical response to diverse environments. Functional and comparative genomics analyses indicate that the marine-derived streptomycetes subgroup possesses some common characteristics of marine adaptation. Our findings have expanded our knowledge of how ocean isolates of streptomycete strains adapt to marine environments.